The 1st. Turkish International Symposium on Deformations - Abdullah, Khairul Anuar (Fakulti Ukur dan Harta Tanah, 1995)
Preamble This write up attempts to report on the conference' on deformation the writer attended in September, 1994 held in Istanbul, Turkey. This report will try to inform the reader on the following; the conference and the organizer, the place, the papers presented and the participants, the social Events and lastly some personal observation on the conference and IstanbuL